Tadeusz Baird. The Composer, His Work, and Its Reception - Literska, Barbara (Eastern European Studies in Musicology, 2020)
This book is the first monographic study of Tadeusz Baird - one of the greatest Polish composers of the second half of the 20th century, a connoisseur of music tradition and a prophet of the future of music (postmodernity), a composer of worldwide renown, an erudite. Baird was deeply engaged in art, aware of the threats and problems of contemporary world, and endowed with a sense of a mission. His personality was shaped by traumatic experiences during World War II and during the late 1940s and early 1950s. He was very demanding of himself and others. As signaled in the title, the book is an extensive, monographic representation of the composer's work and concepts in their stylistic, cultural, and esthetic contexts.